Flowback or the End of Globalization. (January 2014) - Smith, Paul
The processes of globalization have often been described by way of the metaphor of 'flows'—flows of people, goods, capital or ideas. Since the recent worldwide economic recession the nature, direction and vectors of those flows have altered, such that it is time to talk about 'flowback' or even the end of globalization. Looking at flows of people and capital in particular, the article proposes that the changes brought about by the recession were always immanent in the processes of globalization itself and that the recession is best seen as a crisis of globalization. Even if a recovery is underway, the processes of globalization will have been altered forever.